Triple Negative Breast Cancer (TNBC): Possible Biomarkers and Treatments - Sutiono, Dias Rima; Shalannandia, Widad Aghnia (Cermin Dunia Kedokteran, 2017)
Triple negative breast cancer (TNBC) is one of the breast cancer subtype, which account for around 15-20% of overall breast cancer cases. Women with Hispanic or African-American descent are having higher risk factor to develop this type of breast cancer, especially \in their premenopausal period (under 40). This highly aggressive and poor prognosis type of breast cancer does not have several molecular receptors (estrogen receptor, progesterone receptor, and HER2 receptor). The absence of those receptors leads to its insensitivity to hormonal therapies, resulting in limited choice of therapy. Numerous studies have been conducted to discover other potential therapies. The clinical characteristic and other information regarding triple negative breast cancer will be discussed along with several potential prognostic biomarkers and treatments for this cancer.Triple negative breast cancer (TNBC) merupakan salah satu subtipe kanker payudara, yang mencapai 15-20 % kasus kanker payudara secara keseluruhan. Wanita keturunan Hispanik atau Afrika - Amerika lebih berrisiko, terutama dalam periode premenopause (di bawah 40 tahun). Kanker jenis ini sangat agresif dan tidak memiliki beberapa reseptor molekul (reseptor estrogen, reseptor progesteron, dan reseptor HER2). Tidak adanya reseptor mengarah ke ketidakpekaan tumor untuk terapi hormonal, mengakibatkan pilihan terapi terbatas dibandingkan dengan jenis kanker payudara lainnya. Sejumlah penelitian telah dilakukan untuk menemukan terapi potensial lain. Karakteristik klinis dan informasi lain mengenai kanker payudara triple negatif akan dibahas bersama beberapa biomarker prognostik potensial dan pengobatan untuk kanker ini.